Total Phenolic Content and In-Vitro Antioxidant Activity of Coconut Husk Extracts: Effect on Proximate Composition and Texture of Tilapia Surimi Gel: Changes in Proximate Composition and Textural Properties of Tilapia Surimi Gel - Priyadarshini M, Bhargavi; Xavier, Martin; Nayak, Binay Bhushan; Balange, Amjad Khansaheb (Fishery Technology, 2024)
The coconut husk is a waste produced from the coconut industry and is a rich source of phenolic and antioxidant compounds. In this study, the total phenolic content (TPC) and antioxidant activity of the aqueous (TA) and 60% ethanol (TE) extracts were evaluated. The maximum TPC was found in the ethanol extract of coconut husk. The highest DPPH radical scavenging activity of extracts was observed in ethanolic extracts and the highest ABTS activity in aqueous extracts. FTIR analysis revealed the presence of a peak at 1283.84 cm-1 in the ethanol extract and the disappearance of the same peak in the aqueous extract. The extracts at different levels (0.050 (TA-1/TE-1, 0.075 (TA-2/TE-2) and 0.10 (TA- 3/TE-3) % based on protein content) were incorporated into single wash tilapia surimi and quality of gels were investigated. The addition of extracts decreased the pH of the gels. Addition of TA-1, TE-2 and TE-3 resulted in lower expressible moisture content. The pH, hardness and expressible moisture content demonstrated that ethanol extracts of coconut husk can be considered as a potential alternative to commonly used hen egg white powder and other animal based additives to enhance the quality of the freshwater fish surimi.